The effect of using different bed powder in PZT synthesis - N.F.K. Bahanurddin; J.J. Mohamed; Z.A. Ahmad (2016)
In this study, different bedswhich are alumina and PZT powder were used, and their effect on Pb(Zr0.52Ti0.48)O3, (PZT)based ceramics sample was investigated. The mixed powder was pressed by using a hand press at 200 MPa, followed by sintering at 1150 °C for 1 hour. The sintered sample was then characterized by using X-ray diffraction, Field Emission Scanning Electron Microscope, Energy Dispersive X-Ray Analysisand impedance analyzer in order to determine the phase of the element, microstructure and dielectric properties, respectively. The observed microstructure showed that when the alumina was used as the bed powder, the surface of sintered sample that was in contact with alumina powder contained flake structure which represented the alumina element. However, the sample that was sintered with PZT as a bed powder only showed the present of PZT element. From the Archimedes method, the density obtained from the sample that used PZT as bed powder is higher (8.06 g/cm3) compared to the sample that used alumina bed powder (7.9 g/cm3).The dielectric constant measured at 1 kHz is high (2890)and the loss factor islower (0.0852) for the sample used PZT bed powder compared to the sample that used alumina bed powder shows the lower dielectric constant (2715) and high loss factor (0.875). The results showed that PZT powder as the bedpowder wasbeneficialin improvingthe dielectric properties of PZT sample.